2005
DOI: 10.1021/pr050048h
|View full text |Cite
|
Sign up to set email alerts
|

Global Phosphoproteome of HT-29 Human Colon Adenocarcinoma Cells

Abstract: Phosphorylation events in cellular signaling cascades triggered by a variety of cellular stimuli modulate protein function, leading to diverse cellular outcomes including cell division, growth, death, and differentiation. Abnormal regulation of protein phosphorylation due to mutation or overexpression of signaling proteins often results in various disease states. We provide here a list of protein phosphorylation sites identified from HT-29 human colon adenocarcinoma cell line by immobilized metal affinity chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 92 publications
(153 reference statements)
3
91
1
Order By: Relevance
“…The differences in GVBD-inducing ability of the two phosphatases, Cdc25A and Cdc25B, suggest that they have different substrates and nonredundant functions (Solc et al, 2008 (Yaffe et al, 2001;Obenauer et al, 2003). This program has been quite successful and some predictions have been experimentally verified (Gratton et al, 2001;Zhou et al, 2001;Gottlieb et al, 2002;Kim et al, 2002Kim et al, , 2005She et al, 2004;Park et al, 2006;Lemeer et al, 2008). In this study, several strong PKA phosphorylation consensus sites were predicted in Cdc25B including Ser-321 which corresponds to Cdc25-S287 in Xenopus oocytes and human Cdc25B-S323.…”
Section: Introductionmentioning
confidence: 74%
“…The differences in GVBD-inducing ability of the two phosphatases, Cdc25A and Cdc25B, suggest that they have different substrates and nonredundant functions (Solc et al, 2008 (Yaffe et al, 2001;Obenauer et al, 2003). This program has been quite successful and some predictions have been experimentally verified (Gratton et al, 2001;Zhou et al, 2001;Gottlieb et al, 2002;Kim et al, 2002Kim et al, , 2005She et al, 2004;Park et al, 2006;Lemeer et al, 2008). In this study, several strong PKA phosphorylation consensus sites were predicted in Cdc25B including Ser-321 which corresponds to Cdc25-S287 in Xenopus oocytes and human Cdc25B-S323.…”
Section: Introductionmentioning
confidence: 74%
“…The N-terminal region of CR3, residues 267 to 275, contains six demonstrated phosphorylated Ser/Thr sites, which represent 27.2% of the identified LEDGF/ p75 Ser/Thr phosphosites (11,12,15,17,28,36,43,44). These Ser/Thr residues are predicted to be targeted by protein kinase casein kinase 2 (PKCK2) (31).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been proposed that phosphorylation of Ser525 regulates either lamina assembly or its interaction with chromatin (Haas and Jost, 1993;Leukel and Jost, 1995). Tyrosine phosphorylation of lamins has also been described (Otto et al, 2001), and numerous phosphorylation sites have been identified in global, high-throughput or large-scale proteomic studies (Beausoleil et al, 2004;Kim et al, 2005;Olsen et al, 2006). However, the existence, and the functional significance, of the majority of lamin phosphorylation sites remain uncharacterized.…”
Section: Introductionmentioning
confidence: 99%